Audience Reception on Future Anxiety Phenomenon in “Masalah Masa Depan” Music Video by Hindia - Ferry Shandy Welianto Wong; Ido Prijana Hadi; Agusly Irawan Aritonang (Petra Christian University, 2024)
Future anxiety is a condition where individuals experience uncertainty, fear, anxiety, and concern about potential undesirable changes in the future. The varied backgrounds of the informants add appeal to this study. This research aims to understand how the audience interprets the phenomenon of future anxiety in the music video